THE INFLUENCE OF LEADERSHIP AND EMOTIONAL INTELLIGENCE ON EMPLOYEE PERFORMANCE - Syaefullah, Syaefullah; Puspita Sari, I Gusti Ayu Ratih (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This study aims to determine the effect of Leadership and Emotional Intelligence on Employee Performance at PT XYZ., partially and simultaneously uses an associative method with  a quantitative approach, using a sample of 82 people. Collecting data using questionnaires techniques and tools. To find out the description of the respondents' answers and distribution of data using descriptive data analysis techniques. Data processing uses application Microsoft Excel and SPSS version 25. Based on the leadership T test (X1) with employee performance (Y) the t value is 2.240 > t table 1.990 with significant 0.028 <0.05 indicating a significant influence of leadership on employee performance and emotional intelligence (X2) with employee performance (Y) obtained t count 3.744 > t table 1.990 with a significant 0.000 <0.05 indicating a significant effect of emotional intelligence on employee performance. There is an influence of Leadership and Emotional Intelligence simultaneously or jointly on employee performance as evidenced by the results of the F test obtained Fcount 19,442 > Ftable 3.11 with a significance of 0.000 <0.05. Leadership, emotional intelligence on employee performance has a contribution of 31.3% while the rest is influenced by other variables not examined.